2020
DOI: 10.2147/ijn.s277645
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic Acid as a Candidate for Cancer Therapy: A Review

Abstract: Gambogic acid (GA), a kind of dry resin secreted by the Garcinia hanburyi tree, is a natural active ingredient with various biological activities, such as anti-cancer, anti-inflammatory, antioxidant, anti-bacterial effects, etc. An increasing amount of evidence indicates that GA has obvious anti-cancer effects via various molecular mechanisms, including the induction of apoptosis, autophagy, cell cycle arrest and the inhibition of invasion, metastasis, angiogenesis. In order to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 128 publications
1
60
0
Order By: Relevance
“…Therapeutic potentials of natural compounds have been extensively evaluated against various diseases for a long time. Gambogic acid is an important member of the herbal medicine and exhibits anti-proliferative activity against in a wide variety of cancer types in experimental studies (Liu et al, 2020;Xu et al, 2012). In the present study, anti-proliferative and antimetastatic activities of gambogic acid were investigated in Saos-2 cell line by in-silico and invitro studies.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therapeutic potentials of natural compounds have been extensively evaluated against various diseases for a long time. Gambogic acid is an important member of the herbal medicine and exhibits anti-proliferative activity against in a wide variety of cancer types in experimental studies (Liu et al, 2020;Xu et al, 2012). In the present study, anti-proliferative and antimetastatic activities of gambogic acid were investigated in Saos-2 cell line by in-silico and invitro studies.…”
Section: Resultsmentioning
confidence: 96%
“…Also, IC50 value of gambogic acid was calculated as 0.88 µM at 48h in Saos-2 cells. Previous studies revealed that gambogic acid exhibited significant toxicity on various cancer types and its IC50 values is around low μM levels in cancer cells (Liu et al, 2020;Xu et al, 2012). The molecular mechanisms of the anticancer activities of gambogic acid could be determined with further biochemical experiments in Saos-2 cells.…”
Section: Effects Of Gambogic Acid On Human Saos-2 Cells Proliferationmentioning
confidence: 99%
“…Three studies investigated the antimyeloma potential of gambogic acid. Gambogic acid is a caged polyprenylated xanthone and the major active ingredient of gamboge secreted from Garcinia hanburryi [ 142 ]. It exhibited pronounced effects against an array of different cancers and was therefore attributed promising therapeutic potential [ 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, poor aqueous solubility and biodistribution combined with multi-targeting capacity led to unavoidable systemic toxicity [ 144 ]. Therefore, numerous studies focused on the minimization of these side-effects by means of nanotechnology [ 142 , 144 ]. The potential of gambogic acid against MM was evaluated in three studies [ 145 , 146 , 147 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation